Cross-language priming effects in bilingual novel metaphor processing - Katarzyna Jankowiak; Anna B. Cieślicka (Scientific Reports)
Abstract This event-related potential study investigates whether semantically related words facilitate the processing of English novel metaphors and how this effect varies across within- and between-language contexts. Spanish-English/English-Spanish bilinguals performed a meaningfulness decision task in response to sentences in English, which included novel metaphors, novel similes, literal, and anomalous sentences. Prime words that were either related to the overall meaning of the target sentences or unrelated were presented either in English (the within-language condition) or Spanish (the between-language condition) before the sentence onset. In the N400 time window, unrelated primes evoked larger amplitudes than related primes in the within-language condition, indicating that conceptual compatibility reduces cognitive effort during early semantic processing. This effect was absent in the between-language condition, likely due to weaker associative links or additional cognitive demands from language switching. In the Late Positive Complex window, related primes imposed higher processing costs, reflecting their incorporation into sentence interpretation, while unrelated primes were dismissed earlier, reducing later-stage cognitive effort. These findings highlight the role of linguistic context in semantic processing, showing that within-language priming enhances efficiency, whereas between-language priming is less effective, particularly for complex novel metaphorical meanings.